Impulsive noise mitigation in wavelet based orthogonal frequency division multiplexing systems - Ali, Maaz Elhag (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Multicarrier Modulation (MCM) is a widely used modulation scheme in broadband communications. It is superior to ordinary Single Carrier (SC) technique in terms of data rate, combating multipath and eliminating the effect of intersymbol interference (ISI) without using complex equalizers. The most common MCM scheme is Orthogonal Fre- quency Division Multiplexing (OFDM) and can be implemented using the Fast Fourier Transform (FFT) for modulation and demodulation. Wavelet-based OFDM as an al- ternative scheme to Fourier-OFDM has been recently adopted in some standards such as the IEEE 1901. This thesis is mainly about mitigating impulsive noise in wavelet- OFDM systems and this was achieved by using two mitigation techniques. The first method was by using blanking technique which is a common technique used in FFT- OFDM systems. This technique was used to mitigate the impulsive noise in all wavelet families under study which were Haar, Daubechies-4 and biorthogonal-4.4. The second technique, the replacing technique, was proposed and developed based on the mathe- matical analysis of the Haar discrete wavelet transform-OFDM. A redundancy in data was found and exploited to mitigate the impulsive noise. However, the performance of both techniques is highly dependent on the selection of threshold values. The results of the first technique showed that all wavelet types have approximately similar BER performance except the Haar wavelet family which had superior BER performance in most cases. Under the assumption of Bernoulli-Gaussian model for impulsive noise and BPSK-OFDM scheme, it was found that both techniques could achieve performance of BER of 1 × 10−4 with 5 dB gain in SNR when the probability of impulsive noise oc- currence ( p = 0.001). Achieving higher performance requires lowering the probability of occurrence. However, Assuming that there is an improper setting of the threshold value below or near the signal level, the replacing technique showed more immunity to errors. For a Haar DWT-OFDM, BPSK modulation and probability of impulsive noise occurrence of p = 0.01, the replacing technique was able to improve performance by 80% above the unmitigated case while this was 30% for the blanking technique when a threshold was set below 10% of its minimum value.